2018
DOI: 10.3389/fmicb.2018.00753
|View full text |Cite
|
Sign up to set email alerts
|

Novel Activity of a Synthetic Decapeptide Against Toxoplasma gondii Tachyzoites

Abstract: The killer peptide KP is a synthetic decapeptide derived from the sequence of the variable region of a recombinant yeast killer toxin-like microbicidal single-chain antibody. KP proved to exert significant activities against diverse microbial and viral pathogens through different mechanisms of action, but little is known of its effect on apicomplexan protozoa. The aim of the present study was to evaluate the in vitro activity of KP against Toxoplasma gondii, a globally widespread protozoan parasite of great me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 40 publications
3
12
0
Order By: Relevance
“…Currently, the treatment drugs for toxoplasmosis include clindamycin, azithromycin, sulfadiazine, pyrimethamine, and atovaquone. To date, the combination of pyrimethamine and sulfadiazine is considered as the frontline treatment for toxoplasmosis (Giovati et al, 2018; Munera López et al, 2019). However, this treatment has several side effects (de-la-Torre et al, 2011), such as bone marrow arrest, hypersensitive reactions, agranulocytosis and megaloblastic anemia (Rothova et al, 1993; Bosch-Driessen et al, 2002; Guaraldo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the treatment drugs for toxoplasmosis include clindamycin, azithromycin, sulfadiazine, pyrimethamine, and atovaquone. To date, the combination of pyrimethamine and sulfadiazine is considered as the frontline treatment for toxoplasmosis (Giovati et al, 2018; Munera López et al, 2019). However, this treatment has several side effects (de-la-Torre et al, 2011), such as bone marrow arrest, hypersensitive reactions, agranulocytosis and megaloblastic anemia (Rothova et al, 1993; Bosch-Driessen et al, 2002; Guaraldo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Healthy mice were inoculated using Pb GFP CON -infected blood of a donor mouse previously incubated for 90 min at 25 °C with Wa F17.12-KT + (100 µg/ml KT), Wa F17.12-KT + (100 µg/ml KT) and mAbKT4, or PBS (control). Five days after inoculations, parasitaemia of the recipient mice ( n = 5 per group) was evaluated and mean values ± SEM, calculated as reported in Bonkian et al [34], are reported. The experiment was repeated twice.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, β-1,3-glucans are microbial cell wall components in charge of maintaining cell morphology and osmotic integrity [33]. Nevertheless, KT action could involve also different pathways, as a recent study reported the apoptotic activity of peptides mimicking KTs against the protozoan parasite Toxoplasma gondii [34]. However, further investigations on human malaria parasites are requested to assess the mechanism of action of KTs.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, there are some other mechanisms include intracellular targets, such as inducing necrotic and apoptotic-like processes, inhibiting mitochondrial ATP synthesis or causing bioenergetics exhaustion [ 46 ]. Moreover, some AMPs interestingly showed the ability to interact selectively with infected enthythrocytes over host cell [ [47] , [48] , [49] ]. Therefore, AMPs represented a new class of peptide inhibitors that can possibly not only block the attachment and entry of human pathogenic protozoa and viruses but also prevent their growth and replication in the host cells.…”
Section: Amps As Alternative Of Conventional Antibiotics For Infectiomentioning
confidence: 99%